White Oaks Genetic and Chemical Diversity Affect the Community Structure of Canopy Insects Belonging to Two Trophic Levels - Elgar Castillo-Mendoza; Leticia Valencia-Cuevas; Patricia Mussali-Galante; Fernando Ramos-Quintana; Alejandro Zamilpa; Miriam Serrano-Muñoz; Juli Pujade-Villar; Efraín Tovar-Sánchez (Diversity)
The hybridization phenomenon increases genetic diversity and modifies recombinant individuals’ secondary metabolite (SMs) content, affecting the canopy-dependent community. Hybridization events occur when Quercus rugosa and Q. glabrescens oaks converge in sympatry. Here, we analyzed the effect of the genetic diversity (He) and SMs of Q. rugosa, Q. glabrescens and hybrids on the community of gall-inducing wasps (Cynipidae) and their parasitoids on 100 oak canopy trees in two allopatric and two hybrid zones. Eighteen gall wasp species belonging to six genera and six parasitoid genera contained in four families were identified. The most representative parasitoid genera belonged to the Chalcidoidea family. Abundance, infestation levels and richness of gall wasps and their parasitoids registered the next pattern: Q. rugosa higher than the hybrids, and the hybrids equal to Q. glabrescens. Oak host genetic diversity was the variable with the highest influence on the quantitative SMs expression, richness and abundance of gall wasps and their parasitoids. The influence of SMs on gall wasps and their parasitoids showed the next pattern: scopoletin > quercitrin > rutin = caffeic acid = quercetin glucoside. Our findings indicate that genetic diversity may be a key factor influencing the dynamics of tri-trophic interactions that involve oaks.